Teachers' Perception of the Implementation of the Independent Curriculum in Elementary Schools - Maulida, Salwa Nazira; Nurmayani; Lubis, Wildansyah; Siregar, Waliyul Maulana; Nasution, Yusra (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
The COVID-19 pandemic has presented major challenges to the education sector in Indonesia, causing learning to lag behind. In response, the government developed the Independent Curriculum, which began to be implemented at UPT SD Negeri 067690 Medan, replacing the 2013 Curriculum. This research aims to examine teachers' perceptions and barriers to implementing the Independent Curriculum. Using descriptive qualitative methods, data was collected through structured interviews and documentation. The results show that teachers have a positive perception of the Independent Curriculum, but face obstacles such as limited information technology, time management, and variations in students' learning abilities. These obstacles require ongoing training and adequate infrastructure support. In conclusion, although the Merdeka Curriculum is well received, adaptive strategies and support are needed to overcome barriers and ensure successful implementation.